Endometrial thickness cut-off value by transvaginal ultrasonography for screening of endometrial pathology in postmenopausal women with bleeding - Gill, Gaganpreet Kaur; Kaur, Navdeep; Gupta, Misha; Shankar, Uma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Postmenopausal bleeding is defined as blood loss occurring at least 12 months after menopause. Aims and objectives were to assess the clinical usefulness and diagnostic accuracy of ultrasonographic measurement of endometrial thickness (ET) in women with postmenopausal bleeding. Methods: It was a prospective study that took place at Government Medical College and Rajindra Hospital Patiala. from June 2018 to May 2019. The study was carried out in 60 patients presenting with postmenopausal bleeding to the OPD of department of obstetrics and gynecology, Government Medical College and Rajindra Hospital, Patiala. Patients with post-menopausal bleeding were included in the study. The endometrial thickness (ET) was measured on TVS. Hysteroscopy was done. Findings were recorded as atrophic endometrium, endometrial hyperplasia, endometrial polyp, fibroid, and endometrial carcinoma (obvious intrauterine growth with necrotic tissue). Endometrial biopsies were taken in all patients. Histopathological examination was done and was considered as the final diagnosis. Data collected was analysed using Microsoft Excel Office software 2019 version 19.11 and Epi info (CDC Atlanta) version 7.2.3.1. Results: The best diagnostic accuracy for TVS was obtained at endometrial thickness of 4 mm. Conclusions: TVS is useful for detecting endometrial pathology with a cut-off value for ET of 4 mm having a high sensitivity. Role of endometrial thickness cannot be undermined for detecting patients at high risk especially with comorbid conditions.